Penerapan Hukum Perlindungan Konsumen Terhadap Kecelakaan Pada Tempat Wisata - Tesalonika, Beatrice; Hutabarat, Sylvana Murni Deborah (Universitas Semarang, 2024)
This article aims to analyze the application of consumer protection law in the accident that occurred at The Geong Glass Bridge, Banyumas. The background of the problem is an accident that resulted in one fatality and three injuries due to the shattering of the bridge's glass, caused by non-compliance with building standards and certifications as well as competency standards in design and construction processes. The urgency of this writing is the importance of legal certainty for consumers and the responsibility of business operators in meeting safety standards according to the law at tourist sites, as well as serving as an evaluation for the government to more strictly enforce regulations related to the licensing of tourist site operations. The novelty of this research lies in the importance of fulfilling legal obligations by business operators in the tourism industry, as well as the options for dispute resolution through litigation and non-litigation channels. This research offers new insights into the responsibilities of business operators in the tourism industry, a topic that has not been extensively studied in the context of consumer protection law in Indonesia. The research findings reveal that business operators have violated the Consumer Protection Law, supported by other laws, and there have also been violations of consumer rights and business operators' obligations, making the victims entitled to compensation as a form of accountability to consumers. This also emphasizes the importance of compliance with standards and permits in the management of tourist sites. This research is expected to encourage stricter government oversight to prevent similar accidents in the future. Penelitian ini bertujuan untuk menganalisis penerapan hukum perlindungan konsumen dalam kecelakaan yang terjadi di Jembatan Kaca The Geong, Banyumas. Latar belakang masalah yaitu kecelakaan yang mengakibatkan satu korban jiwa dan tiga orang terluka akibat pecahnya kaca jembatan, yang disebabkan oleh ketidaksesuaian standar dan sertifikasi bangunan serta standar kompetensi dalam desain serta proses konstruksi. Urgensi penulisan yaitu pentingnya kepastian hukum bagi konsumen dan tanggung jawab dari pelaku usaha dalam memenuhi standar keamanan sesuai undang-undang pada tempat wisata, serta sebagai evaluasi bagi pemerintah untuk lebih menegakan aturan terkait perizinin pengoperasian tempat wisata. Penelitian ini menggunakan metode yuridis-normatif. Kebaharuan penelitian ini terletak pada pentingnya pemenuhan kewajiban hukum oleh pelaku usaha dalam industri pariwisata, serta opsi upaya menyelesaikan sengketa yaitu melalui jalur litigasi dan non-litigasi. Penelitian ini memberikan wawasan baru mengenai tanggung jawab para pelaku usaha di industri pariwisata, topik yang belum banyak dikaji secara mendalam dalam konteks hukum perlindungan konsumen di Indoneisa. Temuan penelitian mengungkapkan pelaku usaha telah melanggar Undang-Undang Perlindungan Konsumen dikuatkan dengan undang-undang lainnya, juga terjadi pelanggaran terhadap hak-hak konsumen dan kewajiban pelaku usaha sehingga korban berhak mendapatkan ganti rugi sebagai bentuk pertanggungjawaban kepada konsumen serta menegaskan pentingnya kepatuhan terhadap standar dan perizinan dalam pengelolaan tempat wisata. Penelitian ini diharapkan dapat mendorong pengawasan yang lebih ketat dari pemerintah untuk mencegah terjadinya kecelakaan serupa di masa depan.